A formação de professoras da Escola Normal do Colégio de Santa Inês: a educação salesiana no Brasil inserida na pedagogia católica (1927-1937) - Rampi, Dorcelina de Fátima (2007)
In this research, the aim is at the educational performance of Salesian Sisters in Brazil that was developed in the Escola Normal Livre anexa ao Colégio de Santa Inês in order to give teacher formation between the years of 1927 ( when the state government approved the Escola Normal Livre anexa ao Colégio de Santa Inês , under the law number 2.269 in December 31st, 1927) to 1937 ( the beginning of the Estado Novo ). Withim this topic, it is possible to deal with different subjects as teacher formation, teacher training school, catholic education, woman and salesian education, alphabetization and gender relation. In order to show the specific teacher profile that was being formed in this catholic institution, pedagogical proposals, objectives, curriculums, school daily, obtained results, layman and catholic references of education developed in this Institution were analysed. Besides, this research presents the value of bringing elements from the past which can be considered nowadays in the pedagogical proposal of Colégio de Santa Inês and to understand what characterized, in the period mentioned, the pedagogical project used in the Escola Normal Livre anexa ao Colégio de Santa Inês and which were the main principles that guided this project, there is a question that guides the research and it is about what the catholic pedagogy was and in what it differred from the layman pedagogy. It is supposed that, as a catholic institution, the Teacher Training School mentioned above, had recourses to religious teaching that supported it and had also recourses to the methods from oficial layman institutions where the pedagogy of the Escola Nova was developed adjusting itself to the educative pattern of the congregation. To this research, the school chronicles, the historical book from the Teacher Training Course and the School Office documents were used. Most of the information refers to the internal life of the Institution. As a conclusion, with this study, it is possible to say that this school followed seriously its organization and working as it was waited as a normal school and assumed in its pedagogical practice the methods of the catholic pedagogy and elements from the Escola Nova pedagogy